THE DELETION OF THE HUMAN AGENT IN ENVIRONMENTAL SCIENCE DISCOURSE: AN ECOLINGUISTIC STUDY - Wagma Farooq (University of Chitral Journal of Linguistics and Literature, 2021)
This study explores the use of the strategy of erasure in environmental science discourses to explore the deletion of the agent. Three environmental science textbooks have been chosen for analysis. Stibbe’s (2015) framework of erasure has been used as a model for analyzing the data. He asserts that the natural world is marginalized in texts through the use of certain linguistic strategies; these strategies run throughout the whole discourse to construct the erasure of the ecosystem. The researchers aim to identify erasure at the level of void, which is the complete erasure or deletion of the agent from these discourses. Stibbe mentions nine linguistic strategies for the construction of erasure in environmental discourses. These strategies are passive voice, nominalization, co-hyponymy, hyponymy, metaphor, metonymy, construction of noun phrases, transitivity patterns and massification. For the construction of void, the researchers have analyzed the strategies of passivization and nominalization. It has been found that these strategies are pervasive in the discourses, thereby deleting the agent and constructing void. The study suggests a new way to look at the language of ecological discourses and proposes further studies on how euphemistic language in these discourses can negatively influence readers.